( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( x + x 1 ) 6 − ( x 6 + x 6 1 ) − 2
If x is a positive real number , then find the minimum value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
What about A.M > G.M inequality. Can't we apply it here.
Log in to reply
Yes, if you can make all terms to be positive.
Oh crap, i forgot if that equation should be "-" i calculated and i forgot to write on "-"
yes you are right !! it seemed like i have seen this somewhere else too.
thanks for mentioning same other problems
Problem Loading...
Note Loading...
Set Loading...
This problem has been posted twice:
X = ( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( x + x 1 ) 6 − ( x 6 + x 6 1 ) − 2 = ( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( x + x 1 ) 6 − ( ( x 3 + x 3 1 ) 2 − 2 ) − 2 = ( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( x + x 1 ) 6 − ( x 3 + x 3 1 ) 2 = ( x + x 1 ) 3 + ( x 3 + x 3 1 ) ( ( x + x 1 ) 3 + ( x 3 + x 3 1 ) ) ( ( x + x 1 ) 3 − ( x 3 + x 3 1 ) ) = ( x + x 1 ) 3 − ( x 3 + x 3 1 ) = ( x 3 + x 3 1 ) + 3 ( x + x 1 ) − ( x 3 + x 3 1 ) = 3 ( x + x 1 ) ≥ 3 ( 2 ) = 6 By AM-GM inequality x + x 1 ≥ 2